Current Development of ROS-Modulating Agents as Novel Antitumor Therapy - Wang, Nan; Wu, Yue; Bian, Jinlei; Qian, Xue; Lin, Hongzhi; Sun, Haopeng; You, Qidong; Zhang, Xiaojin (Current Cancer Drug Targets, 2017)
Compared to normal cells, usually cancer cells are under higher oxidative stress. Elevating intracellular levels of reactive oxygen species (ROS) by introducing excessive ROS or inhibiting antioxidant system may enhance selectively of cancer cell killing by ROS-modulating agents through stress sensitization or stress overload. Meanwhile due to the adaptive response, normal cells may be capable of maintaining redox homeostasis under exogenous ROS. Here we review ROS-modulating agents in different mechanisms and classify them into groups by various targets for illustrating more clearly. At last, we discuss their side effects and the potential troubles of developing these agents and argue that might be an effective strategy for further exploring to modulate the unique redox regulatory mechanisms of cancer cells.
Keywords: antioxidant system